Targeting perioperative hemoglobin in major abdominal surgery - Markatou, M.; Theodoraki, K.; Rizos, D.; Fassoulaki, A. (Journal of Anesthesia and Clinical Research, 2012)
Background: Perioperative transfusion optimization may result in blood saving and minimization of complications associated with blood transfusions. The study aimed to compare units transfused, cytokines and patient outcome in a restrictive versus a liberal transfusion strategy. Materials and methods: We conducted a randomized-controlled study, in a single center, from December 2004 to May 2007. Of the 75 patients scheduled for major abdominal surgery and assessed for eligibility, 58 were randomized and 52 completed the study. Preoperatively, patients were randomly assigned to the Hb 7.7 g dL-1 (restrictive) or to the Hb 9.9 g dL-1 (liberal) group to receive blood transfusion intraoperatively and postoperatively if hemoglobin was below 7.7 g dL-1 or Hb 9.9 g dL-1 respectively. The follow-up for hemoglobin and intervention lasted five days, for cytokine measurements three days and for complications till discharge from the hospital. Units of red blood cells (RBC) per patient and the incidence of transfused patients in each group were the main outcome measure. Results: Median RBC transfused (units/patient) was 0 [interquartile range 0,2] in the restrictive versus 1 [0,3] in the liberal group (p=0.013), and the percentage of patients transfused 36% versus 70% respectively (p=0.027). Postoperative IL-10 levels were higher in the liberal transfusion group 24 h postoperatively (p<0.05). Pooled peak postoperative IL-10 levels correlated with the overall number of units of blood transfused (r2 = 0.38, p = 0.032) as well as with the overall mean duration of storage of blood transfused (in days) (r2 = 0.52, p = 0.007). Complications or time to discharge from hospital did not differ between the groups. Conclusion: In major abdominal surgery, restrictive transfusion decreases RBC requirements and IL-10 levels. The association between IL-10 and transfusion variables indicates that IL-10 may play a role in transfusionassociated immunomodulation. © 2012 Markatou M, et al.
Keywords: Abdominal surgery; Blood transfusion; Complications; Cytokines